MENUJU KELUARGA SAKINAH DENGAN BERSIWAK - Zuhdi, Muhammad (al-Rasῑkh: Jurnal Hukum Islam, 2023)
This study aims to explore how the use of siwak can contribute to creating a sakinah family, namely a family full of tranquility, peace, and affection. Using a qualitative approach with a descriptive method, this study involved 10 Muslim families who routinely use siwak in their daily lives. Data were collected through in-depth interviews, participant observation, and document analysis. The results of the study indicate that the use of siwak is not only beneficial for oral and dental health, but also has high religious value, which can strengthen spiritual and emotional bonds between family members. The habit of using siwak together creates valuable moments of togetherness, improves communication, and reduces stress in the family. Thus, siwak can be an effective way to support the achievement of a sakinah family. This study provides practical recommendations for Muslim families and religious institutions to promote the use of siwak as part of efforts to create harmonious and healthy families.